THE ORIGIN OF MULTICELLULLAR ORGAISMS AND THE DISCOVERY OF TRICHOPLAX. ITS SIGNIFICANCE FOR UNDERSTANDING THE EVOLUTION OF MULTICELLULAR ORGAISMS - JAY PRAKASH NARAYAN (International Journal of Multidisciplinary Research and Studies, 2020)
The origin of multicellular organisms is a key milestone in the history of life on Earth. The evolution of multicellularity has been a subject of intense scientific interest, and many hypotheses have been proposed to explain how this transition occurred. One of the most intriguing discoveries in this area is the microscopic animal Trichoplax adhaerens. This organism is thought to be one of the earliest branching animals, and its simple body plan and unique features have led researchers to propose it as a possible model for the evolution of multicellularity. In this paper, we will discuss the current understanding of the origin of multicellular organisms and the significance of Trichoplax in this field.